Existence of Protected Forest Function as Protection Area - Nikmah Fitriah; Indriati Amarini (Jurnal Dinamika Hukum, 2021)
The enactment of Law No. 41 Year 1999 emphasizes the position of protected forests as protected areas that must be maintained to provide protection for the surrounding area. Law No. 41/1999 stipulates that open-pit mining activities are prohibited in protected forest areas. However, the effectiveness of Law No. 41/1999 is questioned by the issuance of Law No. 19/2004 which still accommodates open-pit mining in protected forest areas with the argument that the law should not apply retroactively. This article uses normative legal research methods, namely normatively examining various related regulations governing the function of protected forests. The results show that the birth of Law No. 19/2004 which allows several mining entrepreneurs to carry out open-pit mining activities in protected forest areas has resulted in protected forest areas being no different from production forest areas. This can threaten the function of protected forest areas as areas that provide protection for surrounding areas from various natural disaster hazards.Keywords: Existence, Function of Protected Forest, Forestry Law